Heavy Equipment Marketing Strategy Analysis With Product Life Cycle (PLC) Approach - Kholidun, Kholidun; Febriansyah, Febriansyah (Dinasti Publisher, 2024)
Heavy Equipment business in Indonesia is quite potential considering the Indonesian government is implementing various development programs in various regions of Indonesia such as the construction of the Woosh Jakarta-Bandung fast train line, the Jakarta-Cikampek elevated toll road, the construction of infrastructure in various other regions of Indonesia, and buildings for public facilities. To maintain a sustainable competitive advantage in a situation like this, there is an approach that must be used. If the company has the technological capability and the ability to adapt to resources, the company can achieve this goal. The purpose of this study is to determine how important the concept of Product Life Cycle (PLC) is in marketing strategy. The method used in this paper is a literature study, namely by reviewing reading sources related to the concept of marketing strategy through the Product Life Cycle approach. Based on the results of several literature studies, it states that a company will generally have better capabilities than its competitors' performance if it is able to apply the Product Life Cycle concept. It can be concluded that the Heavy Equipment marketing strategy through the Product Life Cycle approach that needs to be improved is Product, Price, Place and Promotion can be utilized in the context of the product life cycle concept. At the maturity stage, the recommended marketing strategy is to differentiate services to differentiate yourself from competitors. Develop new markets to expand reach. Conduct more aggressive market penetration to maintain market share. Increase effective marketing promotions and communications.